Black Phosphorus Nanomaterials Regulate the Aggregation of Amyloid‐β. Issue 5 (18th February 2019) - Lim, Yeh‐Jun; Zhou, Wen‐hua; Li, Gao; Hu, Zhi‐Wen; Hong, Liu; Yu, Xue‐Feng; Li, Yan‐Mei
Abstract: Aggregation of amyloid‐β (Aβ) plays important roles in the progression of Alzheimer's disease (AD), and various carbon‐based nanomaterials have been shown to significantly inhibit aggregation of Aβ. A new member of the family of two‐dimensional (2D) nanomaterials, black phosphorus (BP), has been successfully prepared. Compared to other nanomaterials, BP has a higher surface‐to‐volume ratio, so it has strong adsorption ability for Aβ, and can thereby regulate the aggregation of Aβ. Herein, black phosphorus (BP) nanomaterials are proposed to regulate the aggregation of Aβ for the first time, and the corresponding mechanism is clarified. This work provides new insight into the development of BP‐based strategies to prevent amyloidosis. Abstract : The regulation of amyloid fibrillation by black phosphorous (BP) is reported for the first time. Titanium ligand‐modified BP nanosheets with large planes can effectively adsorb Aβ40 monomer and inhibit Aβ40 from forming fibrils, while smaller titanium ligand‐modified BP quantum dots require a higher mass ratio. Computer simulations were also used to investigate the mechanism and indicated that BP nanomaterials can inhibit Aβ40 aggregation by absorbing monomers to prevent them from attaching to fibril ends.